Optimization of Lapping and Polishing of Steel Samples for Nanoindentation Based on SVM-GA - Cheng, Zhichao; Wei, Qianfeng; Wen, Donghui (Frontiers in Materials, 2022)
Nanoindentation test is extensively employed to obtain the mechanics performance of different kinds of materials. In this paper, the general process in lapping and polishing of Q235 steel samples for nanoindentation has been analyzed by considering the pressure (P), rotation speed of the lapping and polishing plate (rp), flow rate of abrasive slurry (Qa) and processing time (t). It is found from the lapping experiments with a full factorial design that the optimized processing parameters is rp of 200 r/min, P of 30 N and t of 4 min considered in this study by considering the material removal rate and subsurface damage. The Central Composite Design method has been used to design the polishing experiments and the Support Vector Machine (SVM) method has been employed to deal with these experimental results, and it is found that the developed SVM model can accurately predict surface roughness under different processing parameters. Then, based on the SVM model the Genetic Algorithm (GA) method is employed to obtain the optimized processing parameters in the polishing process, and it is found from the SVM-GA study that the optimized processing parameters in the lapping process are rp of 108 r/min, P of 33 N, Qa of 20 ml/min and t of 3 min. Finally, a set of nanoindentation tests have been conducted to evaluate the lapping and polishing performance, and it is found that the surface integrity has been significantly improved after the optimization of the lapping and polishing parameters by using the SVM-GA method considered in this study.